Aplikasi Kasir Portabel Berbasis Android Point of Sale Terintegrasi dengan Pencetak - Sholeh, Muchammad; Sinduningrum, Estu; Putri, Astri Nindya (Universitas Islam Sumatera Utara, 2022)
Based on the results of interviews with shop owners, shop owners confirmed that the Newplus Store still uses a manual cash register system and shop owners also agreed to make a portable Android cashier application with the hope that there will be no errors in transactions, buyers don't have to queue too long, shop owners in recapitulating transactions It's easier and the cashier doesn't have to bother writing receipts on the note so there's less chance of loss to the shop or buyer. Furthermore, the flow of this research uses the waterfall. The purpose of this study is to produce an Android-based portable cashier application that can assist in the recapitulation of sales transaction data for Newplus Store owners. The feature of printing customer receipts is also added to this application. The conclusion of this study is the achievement of making a portable android cashier application accompanied by tests carried out on 1 shop owner and 3 employees. By using the Likert scale method to get an average value of 80.9%, this concludes that the Android portable cashier application can already run well and can be used so that it can solve problems in transactions and can recapitulate sales and produce receipt printing for customers.